Urgency of Notary Deed (Deed of Work Agreement Between Worker & Employer) - Basri Basri (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Labor law is the law that regulates the relationship between workers, employers and the government. Labor law functions to protect the interests of workers from the unlimited power of the employer/entrepreneur (Soepomo, 1999: 8-9). To avoid abuse in the relationship between employers and workers, it is necessary to intervene by the government through statutory regulations. This study aims to determine how urgent the work agreement deed is and how important it is to make a work agreement deed for the world of labor. This research uses a sociological juridical approach, research conducted on the real reality of workers, employers and the role of the government in building better labor laws. Based on research at the Manpower Office of Kendari City, the Manpower Office of Southeast Sulawesi Province and workers, there are several violations of labor regulations and also violations against workers so that the importance of work agreement deeds is that the rights and obligations of both parties can be known together and also notary deeds can be authentic evidence for both parties, and also for workers and employers to be more obedient and obedient to the rules concerning manpower and the urgency of a notary deed is for the development of labor law to make it better in the future, and to minimize labor violations.